KPC-33 and ompK37 mutations: Unraveling the mechanism of ceftazidime/avibactam resistance in ST11 carbapenem-resistant Klebsiella pneumoniae - Shulong Zhao; Lin Ye; Shuang Song; Jingfang Sun; Jinfeng Xu; Fei Jiang; Haiquan Kang (PLoS ONE, 2026)
Background Global surveillance indicates rising ceftazidime-avibactam resistance among carbapenem-resistant Klebsiella pneumoniae (CRKP), with sequence type 11 predominating in China. The contribution of bla KPC variants and porin alterations to high-level resistance remains significant. Methods We employed whole-genome sequencing and functional analyses to characterise a CZA-resistant ST11 CRKP isolate recovered from a patient without prior exposure to ceftazidime-avibactam or carbapenems. Results The isolate harboured bla KPC-33 on a non-conjugative plasmid and multiple non-synonymous mutations in the porin gene ompK37, concomitant with high-level resistance to ceftazidime-avibactam and carbapenems while retaining susceptibility to tigecycline, polymyxin B and amikacin. Conclusions bla KPC-33 coupled with OmpK37 alterations underpins dual resistance to ceftazidime-avibactam and carbapenems in ST11 CRKP, underscoring the need for genomic surveillance and rapid detection of this resistance mechanism.